2021
DOI: 10.1155/2021/6803510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ORF7 of SARS-CoV-2 on the Chemotaxis of Monocytes and Neutrophils In Vitro

Abstract: Coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently the most significant public health threat worldwide. Patients with severe COVID-19 usually have pneumonia concomitant with local inflammation and sometimes a cytokine storm. Specific components of the SARS-CoV-2 virus trigger lung inflammation, and recruitment of immune cells to the lungs exacerbates this process, although much remains unknown about the pathogenesis of COVID-19. Our study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Studies on lung type II lung cells (A549) have shown that the open reading framework (ORF) 7 in the genome of the new coronavirus induces the production of the chemokine CCL2 that promotes the chemotaxis of monocytes and reduces the expression of the chemokine IL-8, which recruits neutrophils. ORF7 increases monocytes infiltration, reduces the number of neutrophils, and may have a specific effect on immunological changes in tissues after infection(35). Similarly, for the results of a study of AH suggest that in primary biliary cirrhosis (PBC), there is a functional monocyte disturbance which seems to be primary and may arise at the cellular level and is the way that SARS-CoV-2 could anabasis(36).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on lung type II lung cells (A549) have shown that the open reading framework (ORF) 7 in the genome of the new coronavirus induces the production of the chemokine CCL2 that promotes the chemotaxis of monocytes and reduces the expression of the chemokine IL-8, which recruits neutrophils. ORF7 increases monocytes infiltration, reduces the number of neutrophils, and may have a specific effect on immunological changes in tissues after infection(35). Similarly, for the results of a study of AH suggest that in primary biliary cirrhosis (PBC), there is a functional monocyte disturbance which seems to be primary and may arise at the cellular level and is the way that SARS-CoV-2 could anabasis(36).…”
Section: Discussionmentioning
confidence: 99%